Risk Assessment of Carbamate Pesticides through Vegetable and Fruit Consumption in Thai Population - Anusasanee, Pornphan; Butryee, Chaniphun; Tanaviyutpakdee, Pharrunrat; Karnpanit, Weeraya (Thai Journal of Toxicology, 2021)
This study aimed to characterize risk of carbamates exposure from fruit and vegetables consumption. Estimation of carbamates exposure via fruits and vegetables intake was calculated from food consumption data of Thai people and seven carbamates residues (carbaryl, carbosulfan, carbofuran, methiocarb, methomyl, oxamyl and aldicarb). The test reports on carbamate residues in 55 commodities (948 samples) were obtained as a courtesy of the Food and Drug Administration, Thailand. The results show that there were no risk of carbamates exposures exceeding safety levels both from acute and chronic models. For acute exposure model, the highest risk was found from exposure to carbofuran from orange consumption as 74% of acute reference dose (ARfD). In addition, hazard quotient of carbofuran exposures were found from consumption of guava and yardlong bean as 20 and 14% of ARfD, respectively. For chronic exposure model, hazard quotient values of individual carbamate was extremely low at lower than 1% of acceptable daily intake (ADI) from consumption of single commodity. Risk characterization from total consumption of fruits and vegetables at average level was considerably low, which hazard quotient of carbofuran exposure from fruits and vegetables consumption was only 4.5% of ADI. However, risk estimation from modelling high consumers showed high risk from exposure to carbofuran up to 91% of ADI, following by exposure to aldicarb (10% of ADI).